Protective effects of Cyclosporin-A in splanchnic artery occlusion shock - Squadrito, Francesco (2000)
1. Cyclosporin A (CsA) is an immunosuppressant drug that inhibits nitric oxide (NO) synthase induction in vascular smooth muscle cells. Splanchnic artery occlusion (SAO) shock is a lethal type of shock characterized by a marked vascular dysfunction in which the L-arginine/nitric oxide pathway plays an important role. We investigated whether CsA exerts protective effects in SAO shock by interfering with the L-arginine/nitric oxide pathway. 2. Male anaesthetized rats (n=156) were subjected to clamping of the splanchnic arteries for 45 min. This surgical procedure resulted in an irreversible state of shock (SAO shock). Sham operated animals were used as controls. SAO shocked rats had a decreased survival (86±6 min, while sham shocked rats survived more than 240 min), marked hypotension, increased serum levels of TNF-α, enhanced plasma nitrite/nitrate concentrations (75±7.1 μM; sham shocked rats=1.6±0.5 μM) and enhanced inducible NO synthase (iNOS) protein induction and activity in the aorta. Moreover aortic rings from shocked rats showed a marked hyporeactivity to phenylephrine (PE, 1 nM–10 μM). 3. CsA (0.25, 0.5 and 1 mg kg(−1), 5 min after reperfusion) increased survival rate (SAO+CsA=236±9 min following the highest dose), reverted the marked hypotension, reduced plasma nitrite/nitrate concentration (11±5.2 μM following the highest dose), restored to control values the hyporeactivity to PE, and blunted iNOS protein induction and activity in aortic rings. 4. The present data indicate that in an experimental rat model CsA may have antishock properties related to inhibition of L-arginine/nitric oxide pathway.